2015
DOI: 10.1002/adsc.201400804
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Direct Arylselenation of Anilines by CH Bond Cleavage

Abstract: Abstract:We describe here an efficient and regioselective synthesis of arylselanyl anilines by coppercatalyzed direct arylselenation of arylamines. Using a catalytic amount of copper iodide in dimethyl sulfoxide at 110 8C under an air atmosphere, a range of arylselanyl anilines was obtained directly from substituted diaryl diselenides in moderate to good yields via C À H bond cleavage of aryl amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 85 publications
0
35
0
1
Order By: Relevance
“…of 1a with 1.0 equiv. for H 2 O 2 proved to be the best choices (entries 5, [16][17][18][20][21][22]. of oxidant H 2 O 2 and 15 mol% of NaCl in H 2 O for 6 hr at room temperature, the desired product, 3,5-dimethyl-1-phenyl-4--(phenylselanyl)-1H-pyrazole 3a was obtained in a good yield of 86% (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of 1a with 1.0 equiv. for H 2 O 2 proved to be the best choices (entries 5, [16][17][18][20][21][22]. of oxidant H 2 O 2 and 15 mol% of NaCl in H 2 O for 6 hr at room temperature, the desired product, 3,5-dimethyl-1-phenyl-4--(phenylselanyl)-1H-pyrazole 3a was obtained in a good yield of 86% (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…The difunctionalizations of alkenes is a main procedure for the synthesis of organoselinides, [13][14][15][16][17][18] and the senelynation of electron-rich aromatic compounds is another normal method for obtaining organoselinides. [19][20][21][22][23][24][25][26][27] Despite organoselinides being important in biological activities and in organic synthesis, there are few studies reported on selanyl-substituted pyrazoles, a kind of heteroaryl selinides, and the number of those pyrazoles is limited. Fritsky's group first reported a procedure for the preparation of symmetrical selanyl-substituted pyrazoles with substituted pyrazoles and selenium dioxide in pyridine, which provided the corresponding products in moderate yields.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports available in literature for the synthesis of these selenides via oxidative C–Se bond formation through the C(sp 2 )–H bond activation of arenes (Scheme ). [3d], Alves and co‐workers reported the selenylation of anilines using CuI in DMSO. [5a] The same group reported an alternative method using anilines and PhSeCl as substrates, in glycerol under an inert atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…[3d], Alves and co‐workers reported the selenylation of anilines using CuI in DMSO. [5a] The same group reported an alternative method using anilines and PhSeCl as substrates, in glycerol under an inert atmosphere. [5b] Recently, we reported the oxidative C–Se bond formation of arenes under different conditions: using I 2 /DMSO (under microwave irradiation), as well as KIO 3 / ethylene glycol (with conventional heating).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation